2011
DOI: 10.1021/ie101884h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolytic Cleavage of β-O-4 Ether Bonds of Lignin Model Compounds in an Ionic Liquid with Metal Chlorides

Abstract: The hydrolytic cleavage of β-O-4 ether bonds in lignin model compounds, guaiacylglycerol-β-guaiacyl ether (GG) and veratrylglycerol-β-guaiacyl ether (VG), was studied in 1-butyl-3-methylimidazolium chloride ([BMIM]Cl) with metal chlorides and water. FeCl3, CuCl2, and AlCl3 were found to be effective and functioned catalytically in cleaving the β-O-4 bond of GG, although a number of other metal chlorides are considerably less active. AlCl3 functioned more effectively in cleaving the β-O-4 bond of VG than did Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
90
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 54 publications
1
90
0
Order By: Relevance
“…However, challenges remain for catalytic lignin depolymerization by zeolites because the current zeolite-based catalysis requires high temperature (250°C or above), which leads to faster catalyst deactivation by coking and dealumination (Jia et al, 2011). Furthermore, the high temperature for solid acidcatalyzed lignin hydrolysis process possibly results in extensive side products from condensation reactions (Jia et al, 2011;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, challenges remain for catalytic lignin depolymerization by zeolites because the current zeolite-based catalysis requires high temperature (250°C or above), which leads to faster catalyst deactivation by coking and dealumination (Jia et al, 2011). Furthermore, the high temperature for solid acidcatalyzed lignin hydrolysis process possibly results in extensive side products from condensation reactions (Jia et al, 2011;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the high temperature for solid acidcatalyzed lignin hydrolysis process possibly results in extensive side products from condensation reactions (Jia et al, 2011;Li et al, 2015). Therefore, the development of low-cost zeolite-based catalysts for lignin conversion at mild temperature will enhance lignin conversion to valuable products.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that catalytic oxidation of lignin or lignin derived fragments is interesting as it is expected to yield functionalized chemicals which can be employed in fine chemical synthesis [1]. In this subject, several reports have been appeared in literature largely focused on catalytic reactions of lignin model compounds which could provide useful information for the development of selective and high yield processes of lignin oxidation namely the conversion of lignin to aromatic monomers catalyzed by triflic acid [2], depolymerization of oxidized lignin to aromatics by formic acid [3], oxidation of phenolic and non-phenolic compounds in presence of metal chlorides in ionic liquid medium [4] are some of the significant achievements in the area of lignin valorization. Among the lignin model phenolic monomers, apocynol, 1-(4-hydroxy-3-methoxyphenoxy)-ethanol is commonly studied over many catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The fragmentation of the C OAr linkage tends to generate water-soluble compounds containing phenolic hydroxyl groups [8]. Investigations have been carried out on C O activation of lignin model compounds in solutions [10][11][12][13][14]. Ekerdt and coworkers have studied ␤ O 4 cleavage in ionic liquids/metal solutions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%